SIMBOL PROSESI PENGANTIN JAWA DALAM FILM MANTAN MANTEN TEORI KRITIS JURGEN HABERMAS - Maghfiroh, Laily Rofi'atul; Ridlwan, Muhammad; Suher, Suher (Universitas Negeri Makassar, 2024)
The purpose of this research is to describe the symbol of the Javanese traditional bridal procession in the film Mantan Manten, which is studied according to the clarity, truth, honesty, and accuracy of Jurgen Habermas' critical theory. This research uses a descriptive-qualitative research method. The data for this research is in the form of Javanese bridal procession symbols. The data source in this research is a screenshot image of the film Mantan Manten by Farishad Latjuba related to Jurgen Habermas' critical theory. The data analysis technique uses a way of classifying data in accordance with the focus of the problem. Based on the research results obtained as follows: (1) The clarity of the Javanese bridal procession symbols is in accordance with the clarity indicator, which is not multi-interpreted and easy to understand. (2) The truth of the Javanese bridal procession symbols is in accordance with the truth indicator, namely the meaning of the symbols used in accordance with the explanation in the Qur'an. (3) The honesty of the Javanese bridal procession symbols is in accordance with the honesty indicator, namely the symbols used as they are, not made up or engineered; and (4) The accuracy of the Javanese bridal procession symbols is in accordance with the accuracy indicator, namely the rules that apply in Javanese customs. Javanese bridal procession symbols are rational in accordance with clarity, truth, honesty, and accuracy.